2016
DOI: 10.1016/j.csite.2016.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Performance of a clothes drying cabinet by utilizing waste heat from a split-type residential air conditioner

Abstract: a b s t r a c tIn the present paper a study on the performance of clothes drying cabinet by utilizing waste heat from a split-type residential air-conditioner (RAC) has been carried out. A drying cabinet with a volume of 1 m 3 has been designed and fabricated. The waste heat from the condenser of the RAC with power of 800 W was utilized as a heat source. In the experiments, the RAC was operated to keep a conditioned space at 20°C. The clothes dried made of pure cotton with initial weight varied 3.05 kg, 5.25 k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 10 publications
0
11
0
1
Order By: Relevance
“…Some parts around the house, such as windows, balconies, garages, front gates, and others are used to dry clothes. This drying method interferes with aesthetics [6].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Some parts around the house, such as windows, balconies, garages, front gates, and others are used to dry clothes. This drying method interferes with aesthetics [6].…”
Section: Introductionmentioning
confidence: 99%
“…Clothes drying is one of the important applications in drying [10], it is applied in daily life [11] and is one of the domestic sector that consumes very large amounts of energy [6]. Household clothes dryers are one of the most energy-efficient appliances in the housing sector [12].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies related to enhancement of energy efficiency of VC refrigeration cycle can be found in literature. Some techniques are heat recovery equipment [1,2], installing internal heat exchanger, multi-stages cycle, etc.…”
Section: Introductionmentioning
confidence: 99%